Institutional Obstacles to African Economic Development: State, Ethnicity, and Custom - (:unkn) unknown (My University, 2009)
To account for the African growth tragedy and, in particular, for its causes rooted in governance problems, the institutional legacy that African countries inherited from pre-colonial and colonial times must be considered. Three aspects are examined here. First, the relationship between ethnicity and state performance is bi-directional: if strong ethno-regional identities prevent the emergence of modern citizenship, they themselves constitute an endogenous outcome of continuous state failures. Second, the persistence of informal rules and social norms causes legal dualism, which undermines the credibility of modern statutory law. Third, social customs and norms that hinder socio-economic differentiation and individual capital accumulation lower the performance of indigenous enterprises.
Keywords: African Research